IPOS IN CHINA: CHALLENGES AND OPPORTUNITIES FOR COMPANIES AND INVESTORS - Rodrigues, Danilo; Bartenstein, Christoph; Cai, Lijian; Chang, Henry; Tomicki, Lucas; Torns, Marc (Pensamento & Realidade, 2012)
China’s economy is gaining significant importance in the global economy and local companies have been entering the Chinese stock market. This trend is only going to increase over the next years and the subject will certainly gain importance in the business and academic world. (Ernst & Young Global IPO trends report, 2011) This paper analyzes the performance of Chinese IPOs in the first day of trading and what mechanisms and tactics were in place in the past five years that allowed firms to perform the way they did. Moreover, the paper will also present changes that have recently occurred or are likely to occur in the near future that are going to change stock performance in the first day of trading in the next years. It will end highlighting strategic perspectives for companies pursuing an IPO in China.